2022
DOI: 10.3390/foods11020217
|View full text |Cite
|
Sign up to set email alerts
|

The Quality Changes and Proteomic Analysis of Cattle Muscle Postmortem during Rigor Mortis

Abstract: Rigor mortis occurs in a relatively early postmortem period and is a complex biochemical process in the conversion of muscle to meat. Understanding the quality changes and biomarkers during rigor mortis can provide a theoretical basis for maintaining and improving meat quality. Herein, a tandem mass tag proteomic method is used to investigate the effects of differentially expressed proteins on the meat quality of cattle Longissimus lumborum muscle postmortem (0, 6, and 24 h). The pH, total sulfhydryl content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The muscle tissue enters rigor mortis after slaughter, because the muscles can no longer relax when the supply of ATP is exhausted, markedly decreasing muscle elasticity and increasing its hardness. The subsequent decrease in meat hardness/rigor is caused by proteolytic autolysis of the muscle proteins, combined at the later stage of storage with microbial proteolysis [ 55 , 56 , 57 ]. The decrease in hardness values of PS-L+, PS+L- and PS+L+ was slower than in the control, partly because the carrageenan film had higher air permeability than the plastic wrap, allowing gas exchange with the outside environment and greater water loss from the pork.…”
Section: Resultsmentioning
confidence: 99%
“…The muscle tissue enters rigor mortis after slaughter, because the muscles can no longer relax when the supply of ATP is exhausted, markedly decreasing muscle elasticity and increasing its hardness. The subsequent decrease in meat hardness/rigor is caused by proteolytic autolysis of the muscle proteins, combined at the later stage of storage with microbial proteolysis [ 55 , 56 , 57 ]. The decrease in hardness values of PS-L+, PS+L- and PS+L+ was slower than in the control, partly because the carrageenan film had higher air permeability than the plastic wrap, allowing gas exchange with the outside environment and greater water loss from the pork.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, meat redness and hue angle measured 24 h post-mortem linearly declined, which could be attributable to the exposure of the meat to oxygen upon storage that triggers oxidative metabolism, and as such, produces free radical by-products that ultimately cause myoglobin oxidation resulting in brown pigment metmyoglobin 35 . Meat pH is mostly associated with the biochemistry condition of the muscle at the point of slaughter, which causes rigor mortis to occur 36 . Chan et al 37 identified a link between meat pH and color, with lighter meat indicating a low pH value and dark meat indicating a high pH value.…”
Section: Discussionmentioning
confidence: 99%
“…A higher degree of MLC2 break down was found in beef aged with the M. flavus biostarter. According to Picard et al [ 44 ], Sierra et al [ 45 ], and Ding et al [ 46 ], the degree of degradation of those proteins (MLC2) is one of the indicators associated with the beef myofibrillar proteins’ effective proteolysis, particularly related to the tenderness of meat.…”
Section: Discussionmentioning
confidence: 99%